2009
DOI: 10.1007/s00406-009-0015-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trauma and post-traumatic stress disorder on the treatment response of patients with obsessive-compulsive disorder

Abstract: Few case series studies have addressed the issue of treatment response in patients with obsessive-compulsive disorder (OCD) and comorbid post-traumatic stress disorder (PTSD), and there are no prospective studies addressing response to conventional treatment in OCD patients with a history of trauma (HT). The present study aimed to investigate, prospectively, the impact of HT or PTSD on two systematic, first-line treatments for OCD. Two hundred and nineteen non-treatment-resistant OCD outpatients were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
4
33
0
1
Order By: Relevance
“…Shavitt et al found that patients who reported a history of trauma were more frequently rated as an SRI responder (47.4%) compared with patients without a history of trauma (22.2%) [54]. On the other hand, in this same study, patients with and without a history of trauma did not differ in terms of their response to cognitive behavioral group therapy (60 vs 63% response, respectively).…”
Section: Sles Tles and Outcome In Ocdmentioning
confidence: 72%
See 1 more Smart Citation
“…Shavitt et al found that patients who reported a history of trauma were more frequently rated as an SRI responder (47.4%) compared with patients without a history of trauma (22.2%) [54]. On the other hand, in this same study, patients with and without a history of trauma did not differ in terms of their response to cognitive behavioral group therapy (60 vs 63% response, respectively).…”
Section: Sles Tles and Outcome In Ocdmentioning
confidence: 72%
“…Only one study [54] has attempted to assess the impact of traumatic events on the treatment response of OCD patients to serotonin re uptake inhibitors (SRIs) and cognitive behavioral group therapy in a prospective manner. Shavitt et al found that patients who reported a history of trauma were more frequently rated as an SRI responder (47.4%) compared with patients without a history of trauma (22.2%) [54].…”
Section: Sles Tles and Outcome In Ocdmentioning
confidence: 99%
“…Additionally, the fact that greater rates of aggressive, sexual/religious, and hoarding OC symptoms were found in post-traumatic OCD is also consistent with previous studies linking forbidden thoughts (Fullana et al, 2010), and hoarding behaviors (Cromer et al, 2007a) to traumatic events. Finally, higher scores on obsession, depression and anxiety measures, and greater rates of suicidality, comorbid mood, anxiety, somatoform and impulse control disorders, indicate that post-traumatic OCD may be particularly severe -although the extent to which it is resistant (Gershuny et al, 2008) or more responsive to treatment (Shavitt et al, 2010) is still unclear.…”
Section: Discussionmentioning
confidence: 98%
“…It remains unclear whether trauma and other life events may worsen (Gershuny, Baer, Jenike, Minichiello, & Wilhelm, 2002;Gershuny et al, 2008) or even improve treatment response for OCD (Bogetto, Venturello, Albert, Maina, & Ravizza, 1999;Lo, 1967;Shavitt et al, 2010), in part due to the methodological inconsistencies, including differences in research designs and the composition of study samples (regular vs. treatment resistant OCD patients). A comprehensive assessment of additional factors such as the severity of stressors, the influence of comorbid diagnoses, as well as past treatment history will be required before the clinical implications of our current findings may be apparent (Fontenelle, Cocchi, Harrison, Miguel, & Torres, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, this study found that individuals with comorbid OCD and PTSD reported higher incidences of lifetime major depressive disorder, dysthymic disorder, panic disorder with agoraphobia, and social anxiety disorder than individuals with OCD and no lifetime PTSD diagnosis. The other known study that compared the clinical characteristics of OCD with and without comorbid PTSD in an outpatient sample also showed significantly higher OCD symptom severity for the comorbid group when severity was measured using the six OCD symptom dimensions as reference points rather than one principal symptom type (Shavitt et al, 2010). Thus, preliminary evidence suggests that individuals with comorbid OCD and PTSD have more severe symptoms of OCD and related psychopathology than those without a lifetime history of PTSD.…”
Section: Introductionmentioning
confidence: 87%